Portable shelter as Covid-19 first aid in public spaces / Yazinta Pangestu Wulandari ... [et al.] - Wulandari, Yazinta Pangestu; Anggraeni, Tri Wulan; Mutmainah, -; Rusmawardi, Angga Palaguna; Falah, Irfan Rizqi (2020)
Prevention efforts are continuously being optimized to fight Covid-19, such as implementing Large-Scale Social Restrictions (PSBB). The spread of Covid-19 in Indonesia is increasingly widespread and its handling is not evenly distributed, making a number of regions have to implement the PSBB, but it cannot be continued because economic activity must continue so as not to cause an economic crisis. The opening of various economic facilities and public facilities has further increased the number of sufferers of Covid-19. In the new normal era body temperature checks are always carried out in public places. However, when someone is indicated that Covid-19 has such a high temperature, they are generally asked to go home and isolate themselves. However, not everyone who is indicated has this awareness, thus increasing the potential for the spread of Covid-19. This paper was created with the aim of designing a portable shelter using the design behavioral setting method, healthy buildings, sites and approaches to Covid-19, as a means of first aid for people with indications of Covid-19 symptoms in public places. The result found is a portable shelter with a compact and adaptive concept where the shelter is integrated with rapid tests, mobility to health facilities and is able to adapt to conditions in limited public spaces, above water and in open spaces. In addition, the shelters are designed to be assembled, sterile and to support increased immunity for sufferers.